INSTRUCTED COLLOCATIONS LEARNING AND SPOKEN PROFICIENCY: SOME CONCLUSIVE INSIGHTS - Jeng-yih Tim Hsu (Universitas Negeri Padang, 2015)
The present study explores lexical collocations and their relation to speaking proficiency of Taiwanese EFL college students leaming English for academic purposes (i.e., EAP). The data is obtained from 92 English majors at a national university of science and technology in southern Taiwan. The results show that (a) direct collocation instruction promotes the subjects' performance on their speaking fluency tests, outscoring the other two instruction types; (b) the advanced level students seem to benefit most as they outperformed the .gther three groups after receiving each of the three instruction types (i.e., lexical collocations, single-item vocabulary, and no instruction); and (c) no significant difference can be found between the high-intermediate and intermediate groups with regard to their post-instruction performances. Therefore, the current study concludes that direct collocation instruction deserves immediate attention and calls for a series of systematic studies to be done on the possible connection between lexical collocations and English proficiency ofEFL learners.